INTEGRATION OF PESANTREN-BASED ARABIC LANGUAGE EDUCATION CURRICULUM IN STRENGTHENING THE CHARACTER DEVELOPMENT OF MAHASANTRI - Zakiyatul Abidah; Septiani Fatikhatus Sholikha (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
Islamic higher education is required to produce graduates who combine academic competence with strong Islamic character. This study examines the integration of a pesantren-based Arabic Language Education (PBA) curriculum in strengthening mahasantri character in line with the vision of Universitas Sunan Drajat Lamongan: developing santri-oriented leaders, entrepreneurs grounded in rahmatan lil-‘alamin, graduates with a global outlook, and individuals with akhlaq al-karimah. Using a qualitative case study design, data were collected through interviews, classroom observations, and document analysis involving curriculum administrators, Arabic language lecturers, and mahasantri. Data were analyzed using an interactive model of data condensation, display, and conclusion drawing. The findings reveal that pesantren values are systematically integrated through the alignment of institutional vision, learning outcomes, contextual teaching materials, and lecturers’ role modeling. This integration strengthens santri leadership through maharah al-kalam, fosters an entrepreneurial mindset oriented toward maslahah, enhances global awareness through academic Arabic proficiency, and internalizes akhlaq al-karimah through ethical learning practices. The study confirms that a pesantren-based Arabic Language Education (PBA) curriculum serves as a strategic instrument for holistic character formation in Islamic higher education